Design of Recognition Robot With Video Transmitter - Irawati Irawati; Deasy Kartikasari (Eduvest - Journal of Universal Studies, 2021)
At appliance - comptroller in general still use the special room for watching area of around, and required some fruit of video and one video for every chamber to can watch every occurrence of place of the room. In consequence proposed the application of this for assisting in watcher, because we can implement this video and can watch with long distance. Because this device apply video available for implemented with long distance apply control transmitter as signal consignor and controller receiver as signal receiver, and processing data here apply microprocessor which allotment to be able to crank and programming language here as controller at PC apply two languages Visual Basic for arranging or controller of movement of motor at device video watcher and linguistic assembly as controller at microprocessor in transmitter and receiver. Takenly of this step can facilitate the us in controlling place wanted without having to install the video of each; every room although place there is still cannot be reached with the video attached. With the application of this earn more profit that is minim of amount of videos and can facilitate we see place which have no reached if the videoes just attached by was wall.